Serum levels of osteopontin predict major adverse cardiovascular events in patients with severe carotid artery stenosis. (15th March 2018) - Carbone, Federico; Rigamonti, Fabio; Burger, Fabienne; Roth, Aline; Bertolotto, Maria; Spinella, Giovanni; Pane, Bianca; Palombo, Domenico; Pende, Aldo; Bonaventura, Aldo; Liberale, Luca; Vecchié, Alessandra; et al.
Abstract: Background: Inflammatory mediators in the blood stream and within plaques are key determinants in atherogenesis. Here, we investigated serum osteopontin (OPN) as a potential predictor of poor outcome in patients with severe carotid atherosclerosis. Methods: Carotid plaques and serum were collected from patients asymptomatic ( n  = 185) or symptomatic ( n  = 40) for ischemic stroke. Plaques were stained for lipids, smooth muscle cells, neutrophils, M1 and M2 macrophage subsets and matrix metallopropteinase-9 (MMP-9). Serum levels of OPN and interleukin-6 (IL-6) were determined by colorimetric enzyme-linked immunosorbent assays. Results: Symptomatic patients showed a two-fold increase in serum OPN levels. In both symptomatic and asymptomatic patients, OPN levels positively correlated with intraplaque count of neutrophils, total macrophages, and MMP-9 content. In asymptomatic patients, OPN levels also positively correlated with lipids and M1 macrophage subsets. Receiver operating characteristic curve analysis identified serum OPN concentration of 70 ng/ml as the best cut-off value to predict major adverse cardiovascular events (MACEs). Patients with high OPN levels had more vulnerable plaque phenotype and reduced levels of HDL-cholesterol and IL-6 as compared to low OPN levels. Kaplan–Meier curve confirmed that patients with OPN levels > 70 ng/ml had more MACEs at a 24-month follow-up. In the multivariate survival analysis, OPN levels > 70 ng/ml predicted MACEs, independently of age, gender, and symptomatic status. Conclusion: High circulating OPN levels were strongly correlated with vulnerability parameters within plaques and predict MACEs in patients with severe carotid artery stenosis. Although confirmation is needed from larger trials, OPN could be a promising clinical tool to assess atherosclerotic outcomes. Highlights: High circulating OPN levels predict MACEs in patients with severe carotid artery stenosis. High OPN levels were correlated with intraplaque neutrophil count. OPN correlated with markers of pro-inflammatory (M1) macrophages within plaques.